BIOMETRIC-ENHANCED CAR SECURITY SYSTEM - TIAW, KINGSLEY YUAN KAI (IRC, 2019)
Face recognition has garnered much interest over the last decade, due to the need for reliable personal identification security. At the same time, the Internet of Things (IoT) have also gathered the attention of the masses from high-end technology device makers to average everyday users. These emerging trends are made possible because of the giant leaps made in hardware and software advancements over the years. Eventually, these trends made their ways to the automotive industry as the automotive makers continue to push the boundaries to satisfy customers’ needs for security and safety. Whilst automakers continuously searching for methods to improve the car security system but sometimes their efforts are not enough to keep off the unwavering motives of car thieves. On average, billions of dollars are lost to vehicle theft worldwide annually. This research project focuses on creating a more innovative approach to overcome the flaws in car security system by utilizing the facial recognition and internet of things technology available in the market. The key objective of this research project is to create a robust car security system to overcome security issues such as car theft, car robbery and unauthorized driving (illegal underaged driving). To carry out this research project, the prototype that consists of Raspberry Pi 3B is used as the main computer. This car security system will feature the facial recognition that is powered by OpenCV. Besides, the system is incorporated with a smartphone application which allows the car owner to have some control over the car while receiving alerts and information regarding the car. Pairing wireless connection and GPS enable the car system to send GPS location and other information to the car owner via the internet connection.